Penerapan Manajemen Waktu dalam Mengatasi Perilaku Prokrastinasi Akademik pada Siswa: Sebuah Studi Literatur - Septin Atalia Sallata; Melda Tiara Samaung; Imelda Putri Paliling (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The phenomenon of academic procrastination is a serious obstacle in the world of education, manifesting as a deliberate delay in starting or completing school assignments. This behavior leads to a decline in academic achievement and an increase in student anxiety when approaching deadlines. This article aims to examine the effectiveness of time management as a strategy to reduce academic procrastination behavior in students through a comprehensive literature review. The research method employed is library research, using content analysis techniques on scientific journal articles and previous research findings relevant within the last ten years. The research findings indicate a significant negative correlation between time management and academic procrastination, where the ability to prioritize and adhere to schedules effectively can lower the level of task delay. Furthermore, intervention through guidance and counseling services using self-management techniques has proven to be a strategic solution in enhancing student learning independence. The implications of this study emphasize the importance of the role of Guidance and Counseling teachers in integrating time management training into guidance programs to support students' sustainable academic effectiveness.